O trabalho como dispositivo de atenção em saúde mental: trajetória histórica e reflexões sobre sua atual utilização - Santiago, Eneida; Yasui, Silvio [UNESP] (My University, 2011)
The partnership between Mental Health (MH) and work is present throughout the history of psychiatry. Capitalist society has used and uses the fitness or unfitness for work not only as one of the elements to the definition of "normality", but also as a treatment strategy. In this perspective, one can find a position healing and, more recently, a different proposal put forward by the psychiatric reform that considers also make / produce, the construction of meaning in the work as crucial for subjectivity. This sense is present in therapeutic workshops that seek to value the uniqueness, not to override the differences. The objective of this paper is to reflect on the relationship between Attention in SM / Work. Initially presents three theses, from which this relationship is built historically: 1 - Work as a means of avoiding idleness returning productively to society; 2 - Work as a healing practice, from the prescription, and 3 - Work as a strategy for care and social inclusion. Below, we discuss some questions about therapeutic workshops and income generation in the mental health care as a device for attention and social inclusion.

A parceria entre Saúde Mental (SM) e Trabalho está presente em toda história da psiquiatria. A sociedade capitalista utilizou e utiliza a aptidão ou inaptidão para o trabalho não apenas como um dos elementos para a definição de “normalidade”, mas, também, como estratégia de tratamento. Nesta perspectiva, pode-se encontrar uma posição curativa e, mais recentemente, uma proposta diferenciada defendida pela Reforma Psiquiátrica que considera, além do fazer/produzir, a construção de significação no trabalho como crucial para a subjetividade. Este sentido está presente nas oficinas terapêuticas que buscam valorizar a singularidade, ao não anular as diferenças. O objetivo deste trabalho é o de refletir sobre a relação entre Atenção em SM/Trabalho. Inicialmente apresenta-se três teses, a partir das quais esta relação se constrói históricamente: 1 – O Trabalho como instrumento de evitar a ociosidade retornando à sociedade de forma produtiva; 2 – O Trabalho como prática curativa, a partir da prescrição médica; e 3 – O Trabalho como estratégia de cuidado e inserção social. A seguir, discute-se algumas questões sobre oficinas terapêuticas e de geração de renda na atenção em saúde mental como dispositivo de atenção e de inclusão social.
The device work as mental health care: reflections on the historical trajectory and its current use
Keywords: Mental Health; Public Health; The World of Work; Public Policy; Psychosocial; Saúde mental; Saúde Coletiva; Mundo do trabalho; Políticas Públicas; Atenção psicossocial